Critical library instruction : theories and methods - Accardi, Maria T.; Drabinski, Emily; Kumbier, Alana (Duluth, MN : Library Juice Press, 2010)
"A collection of articles about various ways of applying critical pedagogy and related educational theories to library instruction"--Provided by publisher.
"There's nothing on my topic!" : using the theories of Oscar Wilde and Henry Giroux to develop critical pedagogy for library instruction / Elisabeth Pankl and Jason Coleman -- Information literacy and social power / Jonathan Cope -- Breaking the ontological mold : bringing postmodernism and critical pedagogy into archival educational programming / Lisa Hooper -- Grand narratives and the information cycle in the library instruction classroom / Sara Franks -- Problem-based learning as teaching strategy / Elizabeth Peterson -- Re-visioning the library seminar through a lens of critical pedagogy / Caroline Sinkinson & Mary Caton Lingold -- Negotiating virtual contact zones : revolutions in the role of the research workshop / Margaret Rose Torrell -- Paradigm shift : utilizing critical feminist pedagogy in library instruction / Sharon Ladenson -- Depositories of knowledge : library instruction and the development of critical consciousness / Bryan M. Kopp and Kim Olson-Kopp -- Preparing critically conscious, information literate special educators for Alaska's schools / Thomas Scott Duke, Jennifer Diane Ward, and Jill Burkert -- Information and service learning / John S. Riddle -- Critical pedagogy and information literacy in community colleges / Gretchen Keer -- Making a home : critical pedagogy in a library internship program for high school students / Daren A. Graves, Mary McGowan, and Doris Ann Sweet -- Posing the wikipedia "problem" : information literacy and the praxis of problem-posing in library instruction / Heidi LM Jacobs -- Out of the margins-- into the panels : toward a theory of comics as a medium of critical pedagogy in library instruction / Damian Duffy -- Information literacy standards and the politics of knowledge production : using user-generated content to incorporate critical pedagogy / Maura Seale -- Critical approach to Asia through library collections and instructions in North America : selection of culture and counter-hegemonic library practices / Hiromitsu Inokuchi and Yoshiko Nozaki -- Teaching against the grain : critical assessment in the library classroom / Maria T. Accardi -- Information is personal: critical information literacy and personal epistemology / Troy A. Swanson -- Encountering values : the place of critical consciousness in the competency standards / Benjamin Harris -- Disintermediation and resistance : Giroux and radical praxis in the library / Ruth Mirtz -- The library as "stuck place" : critical pedagogy in the corporate university / Cathy Eisenhower and Dolsy Smith.
Bibliografija iza svakog rada. Autorsko kazalo.
Keywords: Informacijska pismenost; edukacija korisnika; visokoškolske knjižnice